Perinatal characteristics and prevalence of low birth weight infants in the Federation of Bosnia and Herzegovina: prospective multicentric study - Enida Nevačinović; Anis Cerovac; Gordana Bogdanović; Gordana Grgić (Medicinski glasnik, 2018)
Aim: To investigate the prevalence and obstetrical characteristics of low birth weight infants (LBWIs) in ten Cantons of the Federation of Bosnia and Herzegovina (FB&H). Methods: The prospective study included newborns of both genders, gestational age (GA) of 22 to 42 weeks and birth weight (BW) of less than 2,500 grams in the period 1 January 2009 to 31 December 2009. Results: In the observed period, 22897 neonates were born, out of whom 669 (2.9%) had a BW less than 2500 grams (average BW was 1295 grams; SD ± 234.2; a coefficient of variation of 0.58). The average GA was 31.4 weeks of gestation. The average lifespan of mothers was 27.7 years (SD ± 1.2). The average Apgar scor (AS) in the first minute was 4.6 (SD ± 2.1) and in the fifth minute it was 6.6 (SD ± 1.9). The LBWIs were most commonly delivered by primiparas, 317 (47.5%). Of the 669 LBWIs, 411 (61.4%) were born per vias naturalis, with cephalic presentation. The highest number of LBWIs was born in Sarajevo Canton, 3.7%, and Central Bosnia Canton, 3.7%. The lowest prevalence was in Posavina Canton, 1.1%. The largest late fetal mortality was in Central Bosnia Canton, 7.7 ‰. Conclusion: This study has determined a relatively low prevalence of LBWIs and other examined obstetrical characteristics that are in correlation with European and Global World data.
Keywords: neonate; perinatology; pregnancy